2008
DOI: 10.1088/0031-9155/53/3/015
|View full text |Cite
|
Sign up to set email alerts
|

A proposal of an open PET geometry

Abstract: The long patient port of a PET scanner tends to put stress on patients, especially patients with claustrophobia. It also prevents doctors and technicians from taking care of patients during scanning. In this paper, we proposed an 'open PET' geometry, which consists of two axially separated detector rings. A long and continuous field-of-view (FOV) including a 360 degrees opened gap between two detector rings can be imaged enabling a fully 3D image reconstruction of all the possible lines-of-response. The open P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 13 publications
0
79
0
Order By: Relevance
“…1, the central point of the field of view (FOV), where the highest sensitivity is obtained, is opened. In our previous report [1], we showed the following: 1. A long and continuous FOV including a 360-degree open gap between two detector rings can be imaged, allowing a fully 3D image reconstruction of all the possible lines of response (LORs).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…1, the central point of the field of view (FOV), where the highest sensitivity is obtained, is opened. In our previous report [1], we showed the following: 1. A long and continuous FOV including a 360-degree open gap between two detector rings can be imaged, allowing a fully 3D image reconstruction of all the possible lines of response (LORs).…”
Section: Introductionmentioning
confidence: 79%
“…Our previous report [1] also indicated that there is a limited range for the gap width. Figure 2 illustrates an OpenPET geometry having two detector rings of axial length W, separated by a gap G. When G [ W, the FOV becomes axially discontinuous, as shown in Fig.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…31,32 These systems, however, have large detector gaps which might not be adequately recovered using our proposed approach. In this regard, an in depth investigation about the value of our proposed approach to such systems is warranted.…”
Section: Discussionmentioning
confidence: 99%